Examining the Impact of Digitalization on Indigenous Cultural Heritage Preservation in India - Singh, Bhawani; Ashok Kumar (Enigma in Cultural, 2024)
India's rich tapestry of indigenous cultures faces challenges from globalization and modernization. Digital technologies offer potential for preserving and revitalizing cultural heritage. This study explores the impact of digitalization on safeguarding indigenous cultural heritage in India. A mixed-methods approach was adopted. Qualitative data collection involved interviews with cultural practitioners, community leaders, and experts in digital heritage preservation. Quantitative surveys gauged community perceptions of digitalization's impact. Case studies of digital initiatives were analyzed. Findings highlight digitalization's potential for enhancing accessibility, documentation, and transmission of cultural heritage. Challenges include digital divides, intellectual property concerns, and the risk of cultural appropriation. Community engagement and capacity building are crucial for successful implementation. In conclusion, digitalization offers significant opportunities for preserving indigenous cultural heritage in India. A holistic approach involving community participation, ethical considerations, and capacity building is essential to maximize benefits and mitigate risks.